2005
DOI: 10.1681/asn.2004080701
|View full text |Cite
|
Sign up to set email alerts
|

Calorie Restriction Modulates Renal Expression of Sterol Regulatory Element Binding Proteins, Lipid Accumulation, and Age-Related Renal Disease

Abstract: Sterol regulatory element binding proteins (SREBP) are major regulators of fatty acid and cholesterol synthesis. This study found that age-related renal matrix deposition and proteinuria were associated with increased renal expression of SREBP-1 and SREBP-2 and increased renal accumulation of triglyceride and cholesterol. Because calorie restriction (CR) modulates age-related renal disease, it then was determined whether the effects of CR are mediated partially by modulation of renal lipid metabolism. Compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
50
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 51 publications
8
50
0
1
Order By: Relevance
“…Similar to the results obtained for the adiponectin expression and release into the plasma, senescent rats did not show a significant decrease of cardiac (and liver) triglycerides in response to the stimulatory effects of moderate caloric restriction as described before in kidneys from senescent Fischer 344 rats (Jiang et al, 2005), while the stronger stimulus (6 months, -40%) was sufficient in old and in young animals. Others have also shown that 1 week of moderate caloric restriction in young rats did not affect the triglyceride content while after 3 weeks muscular but not liver triglyceride content was reduced .…”
supporting
confidence: 88%
“…Similar to the results obtained for the adiponectin expression and release into the plasma, senescent rats did not show a significant decrease of cardiac (and liver) triglycerides in response to the stimulatory effects of moderate caloric restriction as described before in kidneys from senescent Fischer 344 rats (Jiang et al, 2005), while the stronger stimulus (6 months, -40%) was sufficient in old and in young animals. Others have also shown that 1 week of moderate caloric restriction in young rats did not affect the triglyceride content while after 3 weeks muscular but not liver triglyceride content was reduced .…”
supporting
confidence: 88%
“…Moreover, enhanced expression of MCP-1 in conjunction with significant renal macrophage infiltrates, particularly in the glomeruli, was observed in the HC and MC groups but was absent in the ALT group. These observations are in line with previous studies employing calorie restriction diets showing significant reductions in glomerular VCAM expression [17], renal monocyte/macrophage infiltration, mesangial expansion [18], and development of proteinuria [19].…”
Section: Con (N = 15) Hc (N = 13)supporting
confidence: 92%
“…In one group of animals (n ϭ 8 in each experimental group), after anesthesia (intraperitoneal injection of pentobarbital; Abbott Laboratories, Chicago, IL), blood was drawn from the inferior vena cava, and then the kidneys were removed and processed for biochemical studies that included 1) RNA extraction and real-time quantitative PCR, 2) isolation of nuclei and microsomes and Western blotting, 3) measurement of stearoyl CoA desaturase-1 (SCD-1) enzyme activity, and 4) lipid extraction and lipid composition analysis. In another group of animals (n ϭ 4 in each experimental group), after anesthesia, the kidneys were fixed via in vivo perfusion fixation and the kidneys were processed for 1) periodic acid Schiff (PAS) stain for renal histopathology, 2) oil red O stain for neutral lipids, and 3) immunofluorescence microscopy for extracellular matrix proteins (5,6,12,18,19).…”
Section: Ins2mentioning
confidence: 99%
“…Urine creatinine concentration was determined by Jaffe's reaction of alkaline picrate with creatinine using a Creatinine Companion kit (Exocell). Results were expressed as the urine albumin-to-creatinine ratio (micrograms per milligram) (5,6,12,18,19). Total RNA extraction and real-time PCR.…”
Section: Ins2mentioning
confidence: 99%
See 1 more Smart Citation